DEVELOPMENT OF CULTURAL TOURISM THROUGH THE INTERPRETATION OF INDONESIAN LOCAL WISDOM - aditya nova putra (LIAISON JOURNAL OF BEST, 2022)
Indonesia is an archipelagic country with potential for tourism development due to the cultural richness and diversity, which has the potential for cultural tourism and local wisdom that can increase economic income and which is a great prospect that can bring foreign tourists, so the local government must intervene to preserve and develop cultural tourism. The purpose of this study is to analyze the development of cultural tourism and local wisdom in Central Java. This research is conducted by using a literature review of books, journals, and previous studies related to this study, as well as the SWOT analysis method (Strength, Weakness, Opportunity, Threat). This SWOT analysis is used to analyze the potential for developing culture and local wisdom, and internal and external problems, especially in the districts of Demak, Jepara, and Kudus, which have unique potential and handicraft products that can be developed for the development and improvement of local cultural tourism. The various potentials that Indonesia has through culture and local wisdom are great prospects for inviting foreign tourists, so local government cooperation is urgently needed to preserve and develop cultural tourism and local culture. The Central Java Fair is used as a promotional media in introducing local cultural tourism destinations, and the strategy for developing local cultural tourism is based on the SWOT analysis of local culture. Keywords: Tourism, Cultural tourism, Local Wisdom, Culture, SWOT Analysis